A bibliometric analysis of the relationship between Digital Twins and Health Management: based on the Web of Science (WoS) platform (Research, Society and Development, 2022)
Amidst the development of Industry 4.0, the appropriation of digital tools applied to production and manufacturing of activities represents a challenge for managers in other areas. Digital Twin (DT) technology is based on the integration of different "traditional" tools, such as simulation modeling and sensors, and aims to increase the performance of any process that can be represented virtually. With the increase in population, the demand for more efficient and universal Health Management (HM) has become a challenge of the 21st century. This study aims to analyze the relationship between the field of knowledge DT and HM and their interactions. A bibliometric review was performed using the Web of Science database through the Bibliometrix package and the VOSviewer application to evaluate studies, applications and identify research clusters and future trends. Our study indicates that the applications of DT in HM are focused on the diagnosis and monitoring of chronic diseases and that, so far, there is not a critical mass of knowledge that consolidates a general theory of application of DT and HM. This study identifies a relational hotspot between the integration of a DT in the optimization of resource management and patient care.